What is a COPD-Like Spirometry Test Result in Resource Constrained Settings?. (4th July 2019) - Gianella, Gonzalo E.; Miranda, J. Jaime; Hurst, John R.
Abstract: The diagnosis of chronic obstructive pulmonary disease (COPD), a global health problem, is challenging in resource-constrained settings. Spirometry with an obstructive pattern after the administration of bronchodilators is required for the diagnosis of COPD. Existing COPD treatment guidelines, largely derived from studies performed in populations of cigarette-smokers, recommend pharmacologic interventions with a tendency to include new—and expensive—drugs as first line agents. As the different factors that cause nonsmokers to develop COPD lead to different phenotypes of disease, COPD severity and treatment efficacy cannot be extrapolated to be the same as in the population of smokers. In so doing, current global initiatives may carry risks when trying to over simplify diagnostic approaches and push for standardization of treatment algorithms that are not context-specific. Future work to mitigate the global burden of COPD needs to address the need for new epidemiological data, especially in areas where tobacco use is less prevalent and environmental factors such as domestic air pollution is common.